Leadership and pedagogical innovations as starting points to achieve a quality education - Blanco Figueredo, Lázaro Liusvangs (2017)
The main function of educational leadership is to cope with educational change. However, pedagogical practice shows that not all educational managers are prepared to effectively lead the initiatives and pedagogical innovations that arise in schools to continuously achieve better quality indices. Limitation provoked in the fundamental, by the tendency at world-wide level to conceive the most curricular designs of postgrado oriented towards the formation of competences of professionals for the investigation. It is a methodological error to leave to the spontaneity in the educational directors the development of competences for the management of the innovations, since the management of the quality is conditional of significant way by the scientific and innovative character of the process. It is the objective of this paper to reflect on the contributions of the author through postgraduate activities to the ongoing formation of educational leaders managers of scientific activity and innovation. The design of the postgraduate activities that are proposed has as conception the relations given between the areas: system of knowledge; System skills; Action and the axiological. Based on this curriculum design, a set of training actions for managers and teachers in Cuba has been developed and implemented for eight years, which are proposed in the international course "Leadership and management in scientific and innovation activity".